Motivasi Berhias dan Kaitannya dengan Kepercayaan Diri Remaja Putri di Teratak Baru Pesisir Selatan - Astuti, Puji; Nasril; Zakirman (Malewa: Journal of Multidisciplinary Educational Research, 2023)
This study is motivated by the existence of important phenomena or problems that need to be examined, especially the problem of young women dressing themselves in New Teratak. This study aims to investigate the biogenetic, sociogenetic, and theogenetic reasons young women in Teratak Baru decorate themselves. Seven young women with criteria ranging in age from 19 to 21 participated in the qualitative method with a descriptive approach. The results indicate that young women decorate themselves to please and satisfy themselves, to attract community attention, and to worship Allah SWT. However, some of the seven young women still lack confidence despite having decorated because of physical factors such as acne and body fat, and they also have little understanding of what decoration is permitted in Islam.